Effects of pressing temperature and pressing time onto the properties of binderless particleboard made from rattan furniture waste - Tajuddin, Maisarah; Ahmad, Zuraida; Ahmad, Roszalia; Halim, Zahurin (Journal of Built Environment, Technology And Engineering (JBETE), 2017)
High awareness on the importance of building green structures by utilizing waste materials has given intense ideas on converting wastes to the value-added board. Thus, this study aims to convert rattan furniture wastes into binderless particleboards (BPB) using the hotpressing process at different pressing temperatures of 170 °C, 180 °C, and 190 °C and pressing time of 4, 5, and 6 min. These selfbonded particleboards underwent mechanical and dimensional stability tests according to the Japanese Industrial Standards (JIS A5908). Most of the BPB produced met the minimum strength requirements, although they did not meet the standard requirement for dimensional stability of boards; yet, these board products were still comparable with commercial particleboards in terms of strength. The mechanism of self-bonding that occurred during manufacturing process was the chemical bonding of rattan components and physical consolidation amongst rattan fibers. The disorderly orientation of rattan fibers and some of the ruptured fibers occurred in the BPB produced had affected the board strength. It can be concluded that rattan furniture waste worked well as an alternative material in producing particleboards for structural usage.